Contrastive analysis of cross-language colloquial correspondence in English and Uzbek Languages (Texas Journal of Philology, Culture and History, 2024)
This article deals with the problem of the classification colloquial units into semantic categories in English, and define their equivalents in Uzbek language, as well as determine common or specific features of the contrasted languages, and explain the discrepancies in translation between two languages.